Wavelet Decomposition Pre-processing for Spatial Scalability Video Compression Scheme - Herrou, Glenn; Hamidouche, Wassim; Morin, Luce (2018 Picture Coding Symposium (PCS), 2018)
Scalable video coding enables to compress the video at different formats within a single layered bitstream. SHVC, the scalable extension of the High Efficiency Video Coding (HEVC) standard, enables x2 spatial scalability, among other additional features. The closed-loop architecture of the SHVC codec is based on the use of multiple instances of the HEVC codec to encode the video layers, which considerably increases the encoding complexity. With the arrival of new immersive video formats, like 4K, 8K, High Frame Rate (HFR) and 360° videos, the quantity of data to compress is exploding, making the use of high-complexity coding algorithms unsuitable. In this paper, we propose a lowcomplexity scalable coding scheme based on the use of a single HEVC codec instance and a wavelet-based decomposition as pre-processing. The pre-encoding image decomposition relies on well-known simple Discrete Wavelet Transform (DWT) kernels, such as Haar or Le Gall 5/3. Compared to SHVC, the proposed architecture achieves a similar rate distortion performance with a coding complexity reduction of 50%.